Improvement of Near Vision for Low Vision Patients in National Eye Healthcare Center Cicendo Eye Hospital 2010-2011 - Enoch, Muhammadnur Rachim; Musa, Ine Renata; Nurhayati, Titing (Althea Medical Journal, 2014)
Background: âLow visionâ is a term used refer to a person having a visual acuity of less than 6/18 (20/60) to light perception (LP). People with low vision can still be treated to perceive or see objects, although several limitations occur.Â Treatments for people with low vision include either optical or non-optical devices. This research aims to reveal visual acuity for near vision that can serve as corrective benchmark after devices for near vision are given.Methods: This is a retrospective descriptive research, using medical records fromÂ the National Eye Healthcare Center, Cicendo Eye Hospital, for the period of August 2010âSeptember 2011 as the subject of the research. Approximately 475 patients were listed, 263Â female and 212Â male. The number ofÂ patients with low vision given with corrective device for near vision were 81 patients.Results: The result showed that visual acuity was corrected after corrective devicesÂ for near vision with the size of 1â10 M were given.Conclusions: The highest of overall corrections or improvements for near vision areÂ the one under the category of âsevere visual impairmentâ.Key words: low vision, optical devices, visual acuityÂ Â Peningkatan Penglihatan Jarak Dekat Pada Penderitaâ Low VisionâÂ di RS Mata Nasional Cicendo 2010â2011Â LatarBelakang: